Mother of the bride murder - Meier, Leslie (Meier, Leslie. Lucy Stone mystery., 2024)
As part-time Tinker's Cove, Maine reporter Lucy Stone says "oui" to her daughter's surprise wedding invitation in France, she must also make a different kind of vow--to catch a killer!